Prospective Statewide Study of Universal Screening for Hereditary Colorectal Cancer: The Ohio Colorectal Cancer Prevention Initiative. (5th May 2021) - Pearlman, Rachel; Frankel, Wendy L.; Swanson, Benjamin J.; Jones, Dan; Zhao, Weiqiang; Yilmaz, Ahmet; Miller, Kristin; Bacher, Jason; Bigley, Christopher; Nelsen, Lori; Goodfellow, Paul J.; Goldberg, Richard M.; et al.
Abstract : PURPOSE: Hereditary cancer syndromes infer high cancer risks and require intensive surveillance. Identification of high-risk individuals among patients with colorectal cancer (CRC) needs improvement. METHODS: Three thousand three hundred ten unselected adults who underwent surgical resection for primary invasive CRC were prospectively accrued from 51 hospitals across Ohio between January 1, 2013, and December 31, 2016. Universal Tumor screening (UTS) for mismatch repair (MMR) deficiency was performed for all, and pathogenic germline variants (PGVs) were identified using multigene panel testing (MGPT) in those who met at least one inclusion criterion: MMR deficiency, diagnosed < 50 years, multiple primary tumors (CRC or endometrial cancer), or with a first-degree relative with CRC or endometrial cancer. RESULTS: Five hundred twenty-five patients (15.9%) had MMR deficiency. Two hundred thirty-four of 3, 310 (7.1%; 16% of the 1, 462 who received MGPT) had 248 PGVs in cancer susceptibility genes. One hundred forty-two (4.3%) had a PGV in an MMR gene, and 101 (3.1%) had a PGV in a non-MMR gene. Ten with Lynch syndrome (LS) also had a non-MMR PGV and were included in both groups. Two (0.06%) had constitutional MLH1 hypermethylation. Of unexplained MMR-deficient patients, 88.4% (76 of 86) had double somatic MMR mutations. Testing for only MMR genes in MMR-deficient patients would have missed 18 non-MMR gene PGVs (7.3% of total PGVs identified). Had UTS been the only method used to screen for hereditary cancer syndromes, 38.6% (91 of 236) would have been missed, including 6.3% (9 of 144) of those with LS. These results have treatment implications as 5.3% (175 of 3, 310) had PGVs in genes with therapeutic targets. CONCLUSION: UTS alone is insufficient for identifying a large proportion of CRC patients with hereditary syndromes, including some with LS. At a minimum, 7.1% of individuals with CRC have a PGV and pan-cancer MGPT should be considered for all patients with CRC.